Approaches for teaching literature used by (T)esl trainees during teaching practice (an analysis of lesson plan) - Cynthia, Aling (Universiti Malaysia Sarawak, UNIMAS, 2009)
TThis study attempt to identify the different approaches and combination of approaches used by (T)ESL trainees of University Malaysia Sarawak (UNIMAS) to teach the literature component during their teaching practicum in schools. The study was conducted using the method of lesson plans analysis whereby 146 literature lesson plans gathered from 25 trainees were analyzed using a checklist where it served as the main instrument for this study. The checklist was consists of six main approaches i.e. information-based approach, personal-based approach, language-based approach, paraphrastic approach, moral-philosophical approach and stylistic approach where the analysis were done by identifying the criteria stated in each approaches. Set induction, input and output of the lesson plans were analyzed based on the criteria in the checklist. Each approaches and patterns found were calculated using frequency count and percentage. The approaches and methods were identified whilst the reasons for employing the approaches were explicated. The findings of this study show that the information-based approach is the most used approach in conducting literature lessons. This also suggested teacher-centred teaching was common among them. An analysis of the pattern used for teaching literature conveyed the structure of using information-based approach in set induction and input and a shift of using language-based approach in output.